Cargo delivery on demand from photodegradable MOF nano-cages. Issue 15 (9th February 2017) - Epley, Charity C.; Roth, Kristina L.; Lin, Shaoyang; Ahrenholtz, Spencer R.; Grove, Tijana Z.; Morris, Amanda J.
Abstract : The photo-induced degradation of and cargo release from a nanoscale metal–organic framework (nMOF) incorporating photo-isomerizable 4, 4′-azobenzenedicarboxylate (AZB) linkers. Abstract : We report the photo-induced degradation of and cargo release from a nanoscale metal–organic framework (nMOF) incorporating photo-isomerizable 4, 4′-azobenzenedicarboxylate (AZB) linkers. The structure matches a UiO-type framework where 12 4, 4′-azobenzenedicarboxylate moieties are connected to a Zr6 O4 (OH)4 cluster, referred to as UiO-AZB. Due to the incorporation of photo-isomerizable struts, the degradation of UiO-AZB is accelerated by irradiation with white light (1.3 ± 0.1% h −1 under dark conditions vs. 8.4 ± 0.4% h −1 when irradiated). Additionally, we show slow release of Nile Red (NR) which is triggered by irradiation (0.04 ± 0.01% h −1 under dark conditions vs. 0.36 ± 0.02% h −1 when irradiated).